Evaluación de un asfalto modificado con aditivo para mejorar sus propiedades mecánicas y de desempeño - Arreaga David, Eddy Bolívar (2025)
The performance of asphalt pavements is closely linked to the quality of the asphalt used in its construction. This study examines the effect of the inclusion of a specific additive on the improvement of its mechanical properties and its response to various loading and climate conditions. To this end, exhaustive characterization tests were carried out, evaluating parameters such as viscosity, resistance to deformation and thermal stability. The results obtained indicate that the selected additive provides significant improvements, increasing the resistance of the asphalt to aging and optimizing its elastic recovery capacity. This indicates that the proposed adjustment could be an effective option to extend the durability of the pavements and reduce maintenance expenses............